Assessment of nutritional status and its association with anthropometric measurements, blood results and body composition in elderly cardiovascular patients - Öztürk Arıkbuka, Müjgan; Yücecan, Sevinç (Progress in Nutrition, 2016)
Background and Aim of the work: This study is planned and applied to analyse nutritional status of elderly patients hospitalized with cardiovascular diseases, in order to identify the association of nutritional status with anthropometric measurements, body composition, blood results, and also to assess the alteration of nutritional status during hospital stay. Methods: Two hundred and eleven 65+ years old patients hospitalized in Dr. Burhan Nalbantoğlu State Hospital’s cardiology and cardiovascular surgery wards more than 3 days were included in the study. Body weight, height, middle upper arm circumference and calf circumference were measured and body composition was assessed with Bioelectrical Impedance Analysis technique, while blood results were recorded from the patients’ files both at admission to and discharge from hospital. Furthermore nutritional status was assessed with full Mini Nutritional Assessment. Results: According to full Mini Nutritional Assessment, on admission 8.5% of patients were malnourished and 43.10% had malnutrition risk while 9.5% of patients were malnourished, 47.4% had malnutrition risk at discharge. Having heart failure increases malnutrition risk 2.84 times when compared to patients having other cardiovascular diseases (p=0.005). Mean albumin, total protein, haemoglobin, body weight, body mass index, middle upper arm circumference and calf circumference values were significantly lower in malnourished and at risk patients than the ones with normal nutritional status both on admission and discharge (p